KONTROLA OŚRODKA POMOCY SPOŁECZNEJ PRZEZ KOMISJĘ REWIZYJNĄ RADY GMINY - Dobkowski, Jarosław (Civitas et Lex, 2018)
The paper deals with the issue of control of the municipal social welfare center performed by the commune council revision commission. The proper considerations were preceded by remarks regarding the principles of organization and functioning of the local government administration in the commune. Against this background, the legal position of the social welfare center, its manager, self-government employees, including social workers was characterized. The legal nature of the revision committee was also referred to and the legal basis for its operation was presented. The rights of the revision committee to the social assistance center were discussed, and the principles and course of the control made by it were approximated. Attention was paid to the diversity of control items. In particular, a significant problem of protection of personal data of the manager and employees of the center during the control was pointed out.